Comparison of Real-World Outcomes of Infliximab versus Adalimumab in Biologic-Naïve Korean Patients with Ulcerative Colitis: A Population-Based Study - Han, Minkyung (Yonsei Med J, 2020)
PURPOSE: Data on the comparative effectiveness of infliximab (IFX) or adalimumab (ADA) in patients with ulcerative colitis (UC) are extremely limited, especially in the Asian population. We compared clinically important outcomes [colectomy, UC-related emergency room (ER) visits, UC-related hospitalizations, and need for corticosteroids] for these two biologics in biologic-naïve Korean patients with UC. MATERIALS AND METHODS: Using National Health Insurance claims, we collected data on patients who were diagnosed with UC and exposed to IFX or ADA between 2010 and 2016. RESULTS: A total of 862 new users of biologics were included, of whom 630 were treated with IFX and 232 were treated with ADA. Over a median follow-up of 1.8 years after starting biologic therapy, there were no significant differences in the risk of colectomy [adjusted hazard ratio (aHR), 1.87; 95% confidence interval (CI), 0.30–11.63], ER visits (aHR, 1.58; 95% CI, 0.79–3.16), hospitalizations (aHR, 0.83; 95% CI, 0.59–1.17), and corticosteroid use (aHR, 1.16; 95% CI, 0.76–1.78) between IFX and ADA users. These results were stable even when only patients who used biologics for ≥6 months were analyzed. Additionally, these results were unchanged in patients treated with biologic monotherapy or combination therapy with immunomodulators. CONCLUSION: In this nationwide population-based study, there was no significant difference in the risk of colectomy, ER visits, hospitalizations, and corticosteroid use between IFX and ADA users. Our findings indicate that IFX and ADA have comparable effectiveness in biologic-naïve Korean patients with UC.